2019
DOI: 10.1038/s41598-019-42709-6
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic and biotic factors controlling fine root biomass, carbon and nutrients in closed-canopy hybrid poplar stands on post-agricultural land

Abstract: Fine roots (diameter <2 mm) have a pivotal role in resource acquisition, symbiosis development, and for elemental cycling in forests. Various abiotic and biotic factors affect their biomass and nutrient content. Understanding the effect of these factors on root traits could improve biogeochemical modelling, nutrient management and ecosystem services provision in planted forests. Data from 14-year old poplars planted along a fertility/climatic gradient in Southeastern Canada, show that live fine root biomass va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 72 publications
0
16
0
Order By: Relevance
“…Hundreds of images can be taken within a short period and have proven to provide reliable information related to foliar and moisture nutrient content, plant health, water content composition parameters for seeds, and leaf area index, applying different vegetation indexes [ 3 , 15 , 23 ]. Other sensors, such as thermal and chlorophyll fluorescence, can also be integrated to detect abiotic and biotic stresses and photosynthetic performance [ 24 , 25 , 26 , 27 ]. The choice of optical sensors mainly depends on the phenotypic variation of interest and image acquisition conditions [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hundreds of images can be taken within a short period and have proven to provide reliable information related to foliar and moisture nutrient content, plant health, water content composition parameters for seeds, and leaf area index, applying different vegetation indexes [ 3 , 15 , 23 ]. Other sensors, such as thermal and chlorophyll fluorescence, can also be integrated to detect abiotic and biotic stresses and photosynthetic performance [ 24 , 25 , 26 , 27 ]. The choice of optical sensors mainly depends on the phenotypic variation of interest and image acquisition conditions [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Current global carbon cycle modeling and budgeting efforts draw on a vast literature regarding patterns and controls of total and aboveground net primary productivity from local to global scales (2,(9)(10)(11). However, the carbon allocated belowground cycles at different rates and is governed by different drivers than aboveground carbon (12). Individual field studies have shown contrasting BNPP responses to environmental variables.…”
mentioning
confidence: 99%
“…Thinning can impact fine root traits through the alteration of biotic and abiotic factors in stands 22 ; however, these studies did not provide any consistent conclusions. For example, some studies showed that fine root biomass decreased in thinned plots 23 , 24 , while others revealed different patterns 25 27 .…”
Section: Introductionmentioning
confidence: 73%